The Effect of Nefopam on Postoperative Fentanyl Consumption: A Randomized, Double-blind Study - Moon, Jee Youn; Choi, Sang Sik; Lee, Shin Young; Lee, Mi Kyung; Kim, Jung Eun; Lee, Ji Eun; Lee, So Hyun (The Korean journal of pain, 2016)
Nefopam is a non-opioid, non-steroidal, centrally acting analgesic drug. The concomitant use of opioids and nefopam is believed to have many advantages over the administration of opioids alone for postoperative pain management. We conducted a randomized, double-blind study to determine the fentanyl-sparing effect of co-administration of nefopam with fentanyl for postoperative pain management via patient controlled analgesia (PCA). Ninety female patients who underwent laparoscopic total hysterectomy under general anesthesia were randomized into 3 groups, Group A, fentanyl 1,000 µg; Group B, fentanyl 500 µg + nefopam 200 mg; and Group C, fentanyl 500 µg + nefopam 400 mg, in a total volume of 100 ml PCA to be administered over the first 48 h postoperatively without basal infusion. The primary outcome was total fentanyl consumption during 48 h; secondary outcomes included pain scores and incidence of side effects. Eighty-one patients were included in the analysis. The overall fentanyl-sparing effects of PCA with concomitant administration of nefopam during the first 48 h postoperatively were 54.5% in Group B and 48.9% group C. Fentanyl use was not significantly different between Groups B and C despite the difference in the nefopam dose. There were no differences among the three groups in terms of PCA-related side effects, although the overall sedation score of Group B was significantly lower than that of Group A. The concomitant administration of nefopam with fentanyl for postoperative pain management may allow reduction of fentanyl dose, thereby reducing the risk of opioid-related adverse effects.